Experimental replication of early human behaviour in bird preparation: a pilot-study focusing on bone surface modification and breakage patterns - Nabais, Mariana; Rufà, Anna; Igreja, Marina (Frontiers in Environmental Archaeology, 2024)
The origin of complex behaviour amongst early humans is a subject of heated debate within the scientific community, and the study of small prey remains has become a significant aspect when examining such modern behaviour. Nonetheless, the consumption of small prey by human populations poses analytical difficulties due to the often negligible, or entirely absent, traces on bone surfaces. To address this difficulty, an experimental study focusing on terrestrial avifauna has been prepared, and here we present a preliminary phase of this research. The aim is to distinguish potential modifications on bird bone surfaces and fracture patterns that might facilitate the recognition of human manipulation of avian skeletal remains. Building upon the challenges encountered in the study of archaeological findings recovered from recent excavations in Iberian Middle Palaeolithic sites, the experimental protocol was formulated to encompass the processing of two uncooked and three roasted birds; and the lithic use-wear analysis of the flint flake used in the processing of raw birds. The results showcase distinct patterns of bone surface modifications and breakage between cooked and uncooked birds. Higher numbers of cut marks and manual disarticulation breaks are found on raw animals, whereas roasted animals show no cut marks, local-specific burns and higher bone loss. This pilot-study provides a baseline for future research to further explore the role of avifauna in Neanderthal subsistence and food processing, which may help highlight cultural choices.